FORMATION A STRATEGY OF AN ENGINEERING COMPANY IN A COMPETITIVE ENVIRONMENT - Y. Aleksandrov (Вестник университета)
The article examines the approaches to the formation of the strategy of innovative development of the engineering companies in the competitive market of engineering services. There is a need to improve the work of companies for the commercialization of innovation that will substantially improve the efficiency and competitiveness of the engineering company. One of the most important stages of this process is the design and pre-sale preparation of the results obtained for its market implementation. The basic directions for the strategy of innovative development of the engineering company OJSC «VTI» are given.